Life cycle assessment of the most representative virgin olive oil production systems in Tunisia - Fernández-Lobato, Lázuli; López-Sánchez, Yaiza; Baccar, Rim; Fendri, Mahdi; Vera, David (Elsevier, 2022)
This study aims to analyze the environmental impacts of Tunisian olive oil production using a “cradle to gate” Life Cycle Assessment (LCA) in order to quantify, compare and establish the most environmentally sustainable practices. This is the first LCA study in Tunisia that covers together the agricultural and industrial activities of one of their most important product value chains. This analysis considers the main olive grove cultivation systems in Tunisia (extensive, intensive, and super intensive) as well as the main extraction systems (press, 3-phase and 2–3 phase combined system). Sixteen categories of environmental impact were assessed following the guidelines set down by the “Product Environmental Footprint Category Rules” for olive oil established by the European Commission. Through the results obtained, it is possible to identify which is the most impactful of the main types of cultivation and extraction systems considered for every impact category individually. As representative values, the impact in climate change category for the most representative value chain (extensive crops and 3 phase extraction) is 3.29 kg CO2 eq. per kg of olive oil without considering biogenic C and 3.53 kg CO2 eq. if biogenic C is considered. The study determines that agricultural activities represent the heaviest contribution in all impact categories for the most representative value chain (from 84.7 % in photochemical ozone formation to 99.9 % in land use). Therefore, efforts should be focused on reducing the impact of the agricultural stage and reaching a high olive oil yield to reduce the overall environmental impact. For that reason, the study proposes to improve efficiency in the agricultural field and continue the investments in the presence of the 2–3 phase combined system.
Keywords: Aceite de oliva -- Producción; Impacto ambiental; Túnez; Olive cultivation; Environmental impacts; Tunisia; Life cycle assessment; Life cycle inventory